Pemberian Kompensasi Dalam Meningkatkan Kinerja Karyawan SPBU â€œXYZâ€ - Iskandar, Iskandar (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The purpose of this research is to determine the effect of compensation on the performance of XYZ gas station employees. To achieve this aim, research was carried out using a sample of 42 people, using the census method (saturated sampling). The data analysis method uses simple linear regression. Based on the test results on the compensation variable (X), the t-count was greater than the t-table (3,151 > 2,021). Thus, it can be concluded that the compensation variable has a positive and significant influence on the performance of XYZ gas station employees. The R. Square (R2) value of 0.557 (55.7%) explains that the compensation variable contributes to the influence on the performance of XYZ gas station employees by 55.7%. Meanwhile, the remaining 44.3% describes other independent variables that were not observed in this study. The recommendation that can be put forward from the recapitulation of the results of respondents' answers to the compensation variable is that it is hoped that the company can provide benefits that are appropriate to the employee's position, because this received the lowest response from respondents.